Efficacy and safety of tranexamic acid administration for subarachnoid hemorrhage: a systematic review and meta-analysis - Eriya Imai; Hiroshi Ito; Hiromu Okano; Akihiko Inoue; Takero Terayama; Hiroshi Okamoto; Toru Hifumi; Yoshihisa Fujimoto; Gaku Fujiwara; Yasuhiro Kuroda (Frontiers in Neurology)
IntroductionAneurysmal subarachnoid hemorrhage (SAH) carries a high risk of early rebleeding and worsens prognosis. Tranexamic acid (TXA), an antifibrinolytic agent, can prevent rebleeding; however, its effects on mortality and neurological outcomes remain controversial.MethodsThis review evaluated the efficacy and safety of TXA with SAH. MEDLINE, CENTRAL, EMBASE, ICTRP, and ClinicalTrials.gov were systematically searched for randomized controlled trials (RCTs) and non-randomized studies of interventions (NRSIs) to assess TXA use in SAH. Studies comparing TXA with controls with SAH were included. The primary outcome was the mortality; secondary outcomes included neurological outcomes, rebleeding, thromboembolism, delayed cerebral ischemia (DCI), hydrocephalus, and adverse events. The certainty of evidence was evaluated using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) approach.ResultsFifteen RCTs (3,109 patients) and nine NRSIs (1,506 patients) were included. RCTs demonstrated that TXA likely does not reduce mortality (risk ratio [RR], 1.00; 95% confidence interval [CI], 0.82–1.22; moderate certainty) and neurological outcome, and may not increase thromboembolism and DCI. However, TXA probably reduces rebleeding but probably increases hydrocephalus. The NRSIs results were similar.DiscussionAlthough routine use is not supported, TXA may be considered for high-risk patients when early aneurysm treatment is unavailable.Systematic review registrationhttps://osf.io/yp78b/.